(untitled) (Castilla. Estudios de Literatura, 2013)
If we understand the rhetoric in a general sense as a manifestation of the persuasive capacities of the speakers, the indigenous peoples they had developed, undoubtedly, before the arrival of the spanish conquerors in 1492, one rhetoric that was transmitted by oral tradition of a generation to other generation. The huehuetlatolli constitute real models of speeches destined for the rhetorical education inside the Aztec culture, which already existed as matter of study in the famous prehispanic calmecac.